2015
DOI: 10.5039/agraria.v10i3a4168
|View full text |Cite
|
Sign up to set email alerts
|

Substituição do milho pelo farelo de algaroba (Prosopis juliflora) em dietas para juvenis de tilápia do Nilo cultivados em baixa temperatura

Abstract: RESUMOO objetivo deste trabalho foi avaliar o farelo de algaroba como substituto do milho em dietas para juvenis de tilápia do Nilo. Foram formuladas quatro dietas experimentais isoproteicas (34% proteína bruta) e isocalóricas (3.150 kcal kg -1 energia digestível) correspondente aos níveis de substituição (0, 33, 66 e 100%) do milho pelo farelo de algaroba. Duzentos e quarenta juvenis de tilápia (1,55 ± 0,02 g) foram alojados em caixas circulares (20 peixes por caixa de 310 L), em um delineamento experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…This fact can be explained by the better feed conversion ratio and the average fish feed intake. A decrease in fish growth performance, however, without any health consequences was observed in the studies of Jesus et al (2011), Sena et al (2012) and Silva et al (2015) of Nile tilapia juveniles fed with MPM of above 20% inclusion in diets. Silva et al (2015), when replacing maize with mesquite meal in juvenile tilapia diets cultivated at low temperatures (20 °C), observed that the survival rate increased linearly with the inclusion levels of mesquite meal in the diet and that the presence of antinutritional factors present in small amounts in the diet would have stimulated the immune system of the fish.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This fact can be explained by the better feed conversion ratio and the average fish feed intake. A decrease in fish growth performance, however, without any health consequences was observed in the studies of Jesus et al (2011), Sena et al (2012) and Silva et al (2015) of Nile tilapia juveniles fed with MPM of above 20% inclusion in diets. Silva et al (2015), when replacing maize with mesquite meal in juvenile tilapia diets cultivated at low temperatures (20 °C), observed that the survival rate increased linearly with the inclusion levels of mesquite meal in the diet and that the presence of antinutritional factors present in small amounts in the diet would have stimulated the immune system of the fish.…”
Section: Discussionmentioning
confidence: 90%
“…A decrease in fish growth performance, however, without any health consequences was observed in the studies of Jesus et al (2011), Sena et al (2012) and Silva et al (2015) of Nile tilapia juveniles fed with MPM of above 20% inclusion in diets. Silva et al (2015), when replacing maize with mesquite meal in juvenile tilapia diets cultivated at low temperatures (20 °C), observed that the survival rate increased linearly with the inclusion levels of mesquite meal in the diet and that the presence of antinutritional factors present in small amounts in the diet would have stimulated the immune system of the fish. The presence of phytochemicals with antioxidant (Sirmah et al, 2011) and antimicrobial (Raja et al, 2012;Thakur et al, 2014) activities has already been confirmed in leaves, wood and bark of the mesquite plant.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, the ADCs (%) of lysine (82.88), methionine (82.57), cystine (83.53) and threonine (82.71) were examined, as these amino acids have basic physiological functions in fish, and are, thus, considered essential (NRC, ). Silva et al () reported ADCs of lysine (88.8%), methionine (95.3%), cystine (99.6%) and threonine (86.1%), which were higher in corn than in MBM.…”
Section: Discussionmentioning
confidence: 97%
“…Silva et al () replaced corn meal (CM) with MBM (by 0%, 33%, 66% and 100%) in low temperature water (20°C) in the diet of tilapia fingerlings (1.55 g), and found no difference in their performance, when compared to a control group. Low water temperatures can result in growth below those expected in Nile tilapia (Santos, Mareco, & Silva, ), thus, in the study by Silva et al (), the effects of MBM may not have been apparent owing to the low temperature of the water.…”
Section: Introductionmentioning
confidence: 99%